One piece : Volumes 52, 53, 54 Sabaody - Oda, Eiichiro; Bates, Megan; Caselman, Lance; Engel, Taylor; Labaamen; Yards, Hudson; Satone, Vanessa; HC Language Solutions (San Francisco, CA VIZ Media, 2016)
Join the adventures--and misadventures--of Monkey D. Luffy and his swashbuckling crew in their search for the "One Piece," the greatest treasure in the world. As a child, Monkey D. Luffy dreamed of becoming King of the Pirates. But his life changed when he accidentally ate the Gum-Gum Fruit, an enchanted Devil Fruit that gave him the ability to stretch like rubber. Its only drawback? He'll never be able to swim gain--a serious handicap for an aspiring sea dog! Years later, Luffy sets off on his quest to find the "One Piece," said to be the greatest treasure in the world. Stopping by the Sabaody Archipelago to get an expert varnish on their ship, the Thousand Sunny, Luffy and his Straw Hat crew run into trouble when they bristle at the local slave trade. Soon the Navy is hot on their trail, and due to the astounding powers of an animalian warlord, Luffy is spirited away to a distant corner of the sea! Will he ever make it back to his crew and achieve his dream of finding the "One Piece"?
Volume 52 Roger & Rayleigh -- Volume 53 Natural born king -- Volume 54 Unstoppable.
This book reads from right to left.
First published in Japan in 1997 by Shueisha Inc. Tokyo.
A compilation of the graphic novel volumes 52-54.
Rated T for Teen. Parental advisory One piece is rated T for Teen and is recommended for ages 13 and up. This volume contains fantasy violence and tobacco usage.
Translated from the Japanese.
112880
Keywords: Luffy, Monkey D. -- Comic books, strips, etc; Pirates -- Comic books, strips, etc; Ability -- Comic books, strips, etc; Treasure troves -- Comic books, strips, etc; Graphic novels -- Japan -- Translations into English; Young adult fiction; Aptitude -- Bandes dessinees; Japan; Young adult fiction; comic books; comic strips; Graphic novels; Comics (Graphic works); Action and adventure comics; Fantasy comics; Fiction; Translations; Young adult works; Teen graphic novels